Meta Analisis Efektivitas Model Pembelajaran STAD Dan Jigsaw Terhadap Peningkatan Sikap Kerjasama Kelas V SD - Galih Mairefa Framanta; Suhandi Astuti (Peneliti.net, 2021)
In this study using Meta-analysis research which aims to determine whether the STAD and Jigsaw learning models have a high influence on improving the cooperative attitude of class V SD. The technique used is the Effect Size technique analysis with the Effect Size formula. The instrument used was the coding data instrument. The variable used to obtain information about the effect size of the Meta Analysis research. From the results of the research that has been done, it shows that the results of the Jigsaw learning model are higher than the STAD learning model, which means that the Jigsaw learning model is more effective in increasing the collaboration attitude of class V SD. Judging from the Ancova test, the average value of Experiment 2 Jigsaw learning model is 70.7505 higher than the STAD 66.6113 learning model. Based on the results of the calculation of the hypothesis using the Ancova test using Univariate which shows that the significance value is 0.001, which means less than 0.05 (0.001 <0.05). From the Ancova test, it shows that F count> F table, namely 11.717 with a significance of 0.001 <0.05, which indicates that Ho is rejected and Ha is accepted. From the results of this test, it shows that the Effect Size of the Jigsaw learning model is significantly larger than the STAD learning model in terms of the cooperative attitude of class V SD.